A Qualitative Study of Discharge Waste Water from Babil / 2 Batteries Factory in Baghdad - A. Musa, Suhair; M.AL-Musawi, Manal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The quality of industrial water from (Babil / 2 batteries factory in Baghdad) was  investigated, and evaluated the physical and chemical characteristics of the water discharged from sections ALShahen , final collection sank. The values were represented by pH, electrical conductivity, biological oxygen demand, chemical oxygen demand ,total suspended solid, total dissolved solid, sulfate, chloride and heavy metal. The sample  of water collocated  by  two samples per month for 6 months  was taking during the period from Novembers 2013 to May 2014. The results show that industrial waste water factory contains contaminations and has varying value rates the average of PH,EC, TDS, SO4, COD, Pb, Zn, for the final collection sank and respectively 8.2,1191.6ïs/cm, 927 mg/L ,722 mg/L,29.2 mg/L, 0.04,mg/L,0.03 mg/L and for Al-Shahen department which also consider final  discharge water but it is separated from final collection sank often acted to Sewerage network PH,EC, TDS, SO4,COD, Zn, Pb, 1.6,12058 ïs/cm, 10122mg/L ,3383 mg/L,203.5 mg/L, 0.4 mg/L, 0.6 mg/L, it is turns of that there is high sulfate  pollution and the value of electrical conductivity was high  and  other materials solid dissolved, heavy metals  and the other parameter  like BOD, CL,TSS,Cd were within the allowable discharge limits.